The dimensions of Religion as underpinning constructs for mass media social marketing campaigns: An emerging concept - Van Esch, Patrick; Van Esch, Linda; Cowley, James (Canadian Center of Science and Education, 2013)
The purpose of this review is to consider the underlying concepts and related issues that have been proposed in the literature of the potential relationship to use the dimensions of religion as constructs for mass media socialmarketing campaigns. The literature appears divided as to whether: (1) an individual’s attitude changes and then their behaviour or (2) behaviour and then attitude, as a result of mass media social marketing campaigns. Whilst the seven dimensions of religion help characterise the constructs and under-pinning themes of religion(s) andtheir existence in the world today, there does not appear to be a definitive approach to the way we professionallypractice, capitalise, use, create or evaluate mass media social marketing campaigns. Whilst both concepts have received and continue to receive growing attention in the literature, further clarification and understanding can only be sought via questions surrounding the emerging concept, which will further assist in distilling the information and possibly provide a new beginning for the study of the concept as well as providing guidance for professional practice.